Progress in Treatment and Diagnostics of Infectious Disease with Polymers - Patra S.; Pareek D.; Gupta P.S.; Wasnik K.; Singh G.; Yadav D.D.; Mastai Y.; Paik P. (My University, 2025)
In this era of advanced technology and innovation, infectious diseases still cause significant morbidity and mortality, which need to be addressed. Despite overwhelming success in the development of vaccines, transmittable diseases such as tuberculosis and AIDS remain unprotected, and the treatment is challenging due to frequent mutations of the pathogens. Formulations of new or existing drugs with polymeric materials have been explored as a promising new approach. Variations in shape, size, surface charge, internal morphology, and functionalization position polymer particles as a revolutionary material in healthcare. Here, an overview is provided of major diseases along with statistics on infection and death rates, focusing on polymer-based treatments and modes of action. Key issues are discussed in this review pertaining to current challenges and future perspectives. © 2024 American Chemical Society.